PROJECT BASED LEARNING SEBAGAI MODEL PEMBELAJARAN RISK BASED AUDIT DENGAN MEDIA APLIKASI AUDIT TOOL LINKED ARCHIVE SYSTEM (ATLAS) - Agung Prajanto (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2020)
The development of auditing methodology has changed along with the advancement of technology and changes in the industry. Auditing standards move from a control based approach to a risk based one. This makes technical auditing more prioritizing the risk that exist in particular entity. This change certainly makes changes in audit methods and learning at  tertiary institutions. Lecturer are required to follow the risk based-audit cycle flow established by international standards on auditing. Lecturer need apply an appropriate learning model to implement a risk based-audit cycle that is project based learning, this model gives student the opportunity to be directly involved in an audit project, identify audit evidence, analyze risk and design reporting at the end of project implementation. Learning will be easier to apply using the ATLAS application media developed by PPPK Ministry of Finance. ATLAS has provided features that have been adapted to the risk-based auditing cycle. Learning with the Project based learning model using the ATLAS application provides a more meaningful experience for student and teachers in exploring risk-based audits. Finally, it encourages student to become auditors and public accountants. Keyword: Project Based Learning, Risk Based Audit, ATLAS